PENGEMBANGAN AGROWISATA TERPADU BERBASIS TANAMAN JERUK DI DESA KERTA KECAMATAN PAYANGAN GIANYAR - Rai, I. N.; Sudama, I. P.; Semarajaya, C. G. A.; Wiraatmaja, W. (Buletin Udayana Mengabdi, 2016)
Kerta village which located at district of Payangan, Gianyar Regency has a unique nature and culture and a wide range of agriculture activities. Those are very potential to be developed into agro-tourism and in turn increasing income and welfare of the community. The most potential of agriculture activities that can be developed to be agro-tourism is citrus farming, because citrus is grown by almost all of paople at the village. The objectived of the community service was to develop citrus farming based integrated agro-tourism. Problems in developing of agro-tourism at Kerta Village were less participation of the community and lack of human resources that capable in this concern including all agro-tourism activities such as packaging tour activities, tourist guiding, brochure preparation, agro-tourism and also having knowledge in cultivation of citrus to produce off-season fruit. The current community service has been successfully solved the problem by providing a complete guide books of agro-tourism at Kerta village which contained information about something to see, something to do, something to buy, and something to learn. Through training and conseling, the community service also increased knowledge and skills of the community in agro-tourism
Keywords: agro-tourism; citrus; commutiy service; Kerta Village